Optimization and performance analysis of water-mediated series indirect evaporative chillers: Experimental and simulated investigation. (15th September 2022) - Jing, Yang; Zhao, Ce; Xie, Xiaoyun; Jiang, Yi
Highlights: The experimental setup can produce cold water below the air wet-bulb temperature. The maximum relative error of developed model is 6.61%. Series indirect evaporative chillers perform better in hot and dry regions. The chiller has excellent anti-freezing properties. Abstract: Evaporative cooling can be applied as a precooling or substitute technology for vapor compression refrigeration systems to save energy and reduce pollution emissions. This paper reports an experimental and numerical investigation of water-mediated series indirect evaporative chillers. An experimental unit was developed for the first time to produce cooling water for a hospital in Xinjiang Province, China. The wet-bulb efficiency of the cooling unit was measured to be above 106.57%, and the dew-point efficiency was 25.81–53.35%. The optimal air and water flow rates in the direct evaporative cooling process are approximately equal and independent of the heat and mass transfer coefficient of the padding. A case study shows that series indirect evaporative cooling is a more befitting process for 63.48% of Beijing's cooling season duration and 36.52% for direct evaporative cooling. The anti-freezing evaluation results show that series indirect evaporative cooling greatly reduces the risk of freezing in cold regions. The performance comparison and flow optimization studies in this paper can provide guidelines for the choice and design of evaporative cooling process. Water-mediated series indirect evaporative cooling performs better in dry and hot regions compared to direct evaporative cooling.